2018
DOI: 10.1002/bimj.201700205
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate multiple test procedures based on nonparametric copula estimation

Abstract: Multivariate multiple test procedures have received growing attention recently. This is due to the fact that data generated by modern applications typically are high-dimensional, but possess pronounced dependencies due to the technical mechanisms involved in the experiments. Hence, it is possible and often necessary to exploit these dependencies in order to achieve reasonable power. In the present paper, we express dependency structures in the most general manner, namely, by means of copula functions. One clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…It is applicable in arbitrary dimensions and generally superior to kernel density or classical and recent copula approaches, with respect to complexity, easy implementation (even in usual spreadsheet programs), and larger scenario VaR estimates. We have tested the procedure described in this paper with the 19-dimensional dataset discussed by Neumann et al (2018) and came to similar conclusions. A crucial point here is the estimation of the marginal distributions which, of course, influences the results to a certain extend, as does the value of m. However, in any case, the original data are exactly reproduced, and the selection of the steering parameters should depend on the purpose of the application.…”
Section: Discussionmentioning
confidence: 56%
“…It is applicable in arbitrary dimensions and generally superior to kernel density or classical and recent copula approaches, with respect to complexity, easy implementation (even in usual spreadsheet programs), and larger scenario VaR estimates. We have tested the procedure described in this paper with the 19-dimensional dataset discussed by Neumann et al (2018) and came to similar conclusions. A crucial point here is the estimation of the marginal distributions which, of course, influences the results to a certain extend, as does the value of m. However, in any case, the original data are exactly reproduced, and the selection of the steering parameters should depend on the purpose of the application.…”
Section: Discussionmentioning
confidence: 56%
“…Model 2.1 is a standard multiple testing model in the context of studies with M endpoints, which are all measured for the same n observational units; see, among many others, [7], [15], and [12]. Under Model 2.1, we make the following general assumptions.…”
Section: Notation and Preliminaries Multiple Testingmentioning
confidence: 99%
“…Dependence modeling by means of copula functions has recently received a lot of attention in multiple testing, see [6], [2], [14], [13], [15], [3], [12], and Sections 2.2.4 and 4.4 of [5]. For example, in [6] it has explicitly been shown that the copula approach leads to the most general construction method for single-step multiple tests under known univariate marginal null distributions of test statistics or p-values, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In order to show the powerfulness of continuous PUC approaches in higher dimensions we conclude the applied section with a discussion of the 19-dimensional data set presented in Neumann et al [5], listed in Tab. For simplicity, we will consider only the Gamma copula in this section.…”
Section: Case Study Bmentioning
confidence: 99%
“…the d-dimensional Lebesgue measure. In this case, is a singular mixture of product densities given by 1 , , d a a  ( ) c u (5) ( ) ( 1 1 ( ) :…”
mentioning
confidence: 99%